A systematic review of the experience, occurrence, and controllability of flow states in elite sport - Swann, C.; Keegan, R. J.; Piggott, D.; Crust, L. (Psychology of Sport and Exercise, 2012)
Objectives: This study aimed to provide an up-to-date summary of the literature on flow in elite sport, specifically relating to: (i) how flow is experienced; (ii) how these states occur; and (iii) the potential controllability of flow. Design: Systematic review. Methods: A comprehensive literature search of SPORTdiscus, PsycINFO, SAGE journals online, INGENTA connect, and Web of Knowledge was completed in August, 2011, and yielded 17 empirical studies published between 1992 and 2011. The primarily qualitative findings were analysed thematically and synthesised using a narrative approach. Results: Findings indicated that: (i) some flow dimensions appear to be experienced more consistently than others; (ii) key factors were consistently reported to induce or inhibit flow occurrence; and (iii) the perception that flow experiences could be controllable to some extent, and are not merely `coincidental`. Additionally, it is appears that physiology is also relevant in flow, and these experiences may be psychophysiological. Conclusions: Based on these findings, recommendations are made including the need for researchers to move from description to explanation of flow, the use of new methodologies, greater focus on the role of personality factors, and possible refinements of existing flow theory to be more specific to sport.